Verimlilik ve Üretkenlik Üzerine Düşünceler - (:unkn) unknown (My University, 2002)
0

This paper discusses the concepts of efficiency and productivity and stresses their importance for countries in crises such as Turkey whose resources are scarce. The first point mentioned is the confusion in the definitions of efficiency and productivity in Turkey In recent years the economy in developed countries is shifting more and more towards service sector, therefore in the second part of the paper service producing systems are considered. It is more diffucult to measure the productivity in service organizations since both input and output have higher varietyand also quality has more influence on the output than manufacturing organizations. So new means of measuring the output should be developed which also include quality. In the service sector, studies related with the measurement of productivity and efficiency need to be widened since the productivity is poor as opposed need to the manufacturing sector. And in the last part of the paper the causes and remedies for the identified inefficiencies in a firm are discussed.